Design of passive fault-tolerant controllers of a quadrotor based on sliding mode theory - Merheb, Abdel-Razzak; Noura, Hassan; Bateman, François (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, sliding mode control is used to develop two passive fault tolerant controllers for an AscTec Pelican UAV quadrotor. In the first approach, a regular sliding mode controller (SMC) augmented with an integrator uses the robustness property of variable structure control to tolerate partial actuator faults. The second approach is a cascaded sliding mode controller with an inner and outer SMC loops.
Keywords: quadrotor UAV control; fault tolerant control; sliding mode control; cascaded SMC; bio-inspired gain tuning